2022
DOI: 10.1097/ju.0000000000002496
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing with a TWIST: Systematic Review and Meta-Analysis of a Testicular Torsion Risk Score

Abstract: Purpose:The Testicular Workup for Ischemia and Suspected Torsion (TWIST) score is a 7-point tool to evaluate acute scrotal pain. Parameters include testicular swelling (2 points), hard testis (2), high-riding testis (1), absent cremasteric reflex (1) and nausea/vomiting (1). This review aimed to determine the diagnostic utility of TWIST and its role in risk stratification.Materials and Methods:A systematic review and meta-analysis of diagnostic test accuracy was conducted. Five risk stratification systems were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“… 66 A recent systematic review and meta-analysis showed that TWIST is a valuable technique for detecting possible TT and is suitable for widespread use, suggesting that it is a helpful tool for making treatment decisions in cases of acute scrotal presentation. 67 Based on our review, we suggested adding one more point to the TWIST score for TT presentation concomitant with sleep. Adopting this upgrade in the TWIST score to confirm the association of sleep as a risk factor for TT requires further investigation through future studies.…”
Section: Discussionmentioning
confidence: 99%
“… 66 A recent systematic review and meta-analysis showed that TWIST is a valuable technique for detecting possible TT and is suitable for widespread use, suggesting that it is a helpful tool for making treatment decisions in cases of acute scrotal presentation. 67 Based on our review, we suggested adding one more point to the TWIST score for TT presentation concomitant with sleep. Adopting this upgrade in the TWIST score to confirm the association of sleep as a risk factor for TT requires further investigation through future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Qin and Qu (page 62) from Australia performed a systematic review and meta-analysis looking at the efficacy of the scores in predicting torsion. 4 Different stratification systems (Barbosa, Sheth and 3 other schemes that group the scores into risk tiers) were compared. They concluded that the original system by Barbosa remains the most reliable but note that there is still room for improvement by increasing the specificity of the intermediate risk group.…”
Section: Diagnosing With a Twist: Testicular Torsion Risk Scorementioning
confidence: 99%
“…Those with a TWIST score of 0–2 are of low risk for TT, a score of 3–4 indicates intermediate risk, and a score of 5–7 points indicates a high risk for TT (Frohlich et al, 2017). Many studies have validated the use of the TWIST score (Barbosa et al, 2014; Frohlich et al, 2017; Qin & Qu, 2022).…”
Section: Risk Factorsmentioning
confidence: 99%